Tree growth response to climate change in two threatened South American Biomes: Brazilian Atlantic Forest and Chilean Mediterranean Forest - Venegas González, Alejandro Danilo (2017)
Biomes classified as Brazilian Atlantic Forest (BAF) and the Chilean Mediterranean forest (CMF) have been affected by anthropic pressure that has caused a considerable decrease of their forest surfasse. However, they are rich in biodiversity and they provide many ecosystem services and were, therefore, classified as \"hotspots\" (forests in risk). Therefore, is essential to study the natural dynamics and the climatic response of the trees of these forests to include conservation projects and strategic measures. To achieve these objectives, the scientific literature reports that tree growth rings are the only ecological indicators with annual resolution that can be efficient and highly accurate to obtain this information. In this context, the research project has as main objective the retrospective analysis of radial growth of forest species in different vegetation communities of BAF and CMF in response to climatic changes. To achieve this goal, four key questions were elaborated: 1) Which variable explains betterthe variability of radial growth at different spatial and temporal scales? 2) What is the growth resilience to recent climate changes? 3) Is there some more vulnerable population to expected climatic changes?. A total of five sites (seven populations) of Cedrela odorata and C. fissilis in BAF from the State of São Paulo in Brazil, and five sites (10 populations) of Nothofagus macrocarpa (FMC) from the central region of Chile were sampled, using a non-destructive method. Four chapters were developed to answer these questions. Chapter I seek to analyze the resilience in radial growth to changes in regional climate variability and droughts, in temporal and spatial scale, on Atlantic forest remnant forests of biogeographic region Serra do Mar. Results show that radial growth in wet sites (winter rains exceed 240 mm) depend on the moisture conditions in dry season, while the higher population is more sensitive to the favorable summer water condition, which would be explained because this population received a lower temperature than the other Cedrela spp. populations studied. Chapter II analyzed how recent climatic variability affected the radial growth in N. macrocarpa populations. It is observed that all the populations are closely linked to the precipitations of May-November (end of autumn/end of spring) and average temperature of October-December (mid-spring/early summer). In Chapter III, we continued exploring the growth responses to climate in the FMC populations in order to find biogeographic differences. In this sense, we evaluated if this significant decrease in tree growth is differentiated between populations and age classes, and determine if the positive effect of CO2 fertilization compensates the precipitation decrease and temperature increase in the last decades in the growth of older, maturer and younger trees . Results show a significant negative trend in all classes from the year 2000, which would be associated to a decrease in precipitation in all populations while temperature was more associated with the northern and southern populations (distribution limit). We did not find a positive effect of rising CO2. Finally, chapter IV integrated the results of the two biomes comparing the projections of aboveground trees biomass under two climatic scenarios of CMIP5 project (light and severe), in order to know which populations are more vulnerable to rising temperature forecasted by year 2100, using ring width data, wood density and allometric equations. This study will provide an overview of adaptation to recent and projected climatic changes of two hotspot neotropical biomes. Although they are different in structure-biodiversity-climate are in risk. Thus, we can understand the vulnerability of threatened forests in South America to global warming that, although they are in protected areas, does not guarantee their persistence.